Enhancing fibroblast–epithelial cell communications: Serpine2 as a key molecule in Fusobacterium nucleatum–promoted colon cancer - Li, Xueke; Luo, Simin; Jiang, Yifang; Ma, Qiong; You, Fengming; Kuang, Qixuan; Fu, Xi; Zheng, Chuan (Frontiers in Immunology, 2025)
BackgroundFusobacterium nucleatum (Fn) has been identified as a causative factor in the progression of colon cancer. This study aims to integrate bulk RNA-seq with single-cell RNA-seq (scRNA-seq) to elucidate the molecular mechanisms by which Fn facilitates colon cancer progression.MethodsThe scRNA-seq data from tumor tissues of Fn intervention were analyzed to screen cells with significant proportion changes. Differentially expressed genes of cells with different proportions were extracted and intersected with those identified in the bulk RNA-seq analysis. Three machine learning algorithms were employed to identify characteristic genes. Clinical tissue samples and external datasets, along with in vitro co-culture experiments, were utilized to validate these findings.ResultsFollowing Fn intervention, there was an observed increase in the fibroblast iso-cellular ratio and interaction levels. Utilizing machine learning algorithms, we identified five key genes. The differential expression of Serpine2 was validated using clinical samples and external datasets. Furthermore, patients with metastatic colon cancer exhibited significantly higher Serpine2 expression compared to those without metastasis. Fn was found to significantly enhance the expression of Serpine2 in fibroblasts and to promote the proliferation and migration capabilities of tumor cells.ConclusionThis study elucidates the role of Fn in promoting colon cancer progression through the enhancement of fibro-macrophage–epithelial cell interactions. Furthermore, Serpine2 has been identified as a potential molecular marker associated with Fn-mediated colon cancer progression and metastasis. These findings contribute novel insights that may inform the development of therapeutic strategies for colon cancer.